A New Experimental Device for Transapical Access of the Aortic and Mitral Valves as well as the Aorta in its Various Segments - Leonardo Paim; José Honório Palma da Fonseca; Francismar Vidal de Arruda Junior; Paulo Sampaio Gutierrez; Luiz Felipe Pinho Moreira; Fabio Biscegli Jatene (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To present the results of a new experimental device developed to facilitate the transapical access in endovascular treatment of structural heart diseases. It aims to reduce the risk of bleeding and complications in this type of access and demonstrate the device as a safe, fast and effective alternative. Methods: CorPoint is composed of three parts: introducer, base with coiled spring, and closing capsule. By rotating movements, the spring is introduced into the myocardium and progressively approaches the base to the surface of the heart. Guidewires and catheters are inserted through the hollow central part and, at the end of the procedure, the capsule is screwed over the base, therefore stopping any bleeding. Results: The device was implanted in 15 pigs, weighing 60 kg each, through an anterolateral thoracotomy, while catheters were introduced and guided by fluoroscopy. All animals had minimal bleeding; introducers with diameter up to 22 Fr were used and various catheters and guidewires were easily handled. After finishing the procedure, the closing capsule was attached and no bleeding was observed at the site. Conclusion: This new device has proved effective, fast and secure for the transapical access. This shows great potential for use, especially by ensuring an easier and direct access to the mitral and aortic valves; the shortest distance to be traveled by catheters; access to the ascending and descending aorta; decreased bleeding complications; decreased surgical time; and the possibility of allowing the technique to evolve and become totally percutaneous.